Salivary Interleukin-6 as a Non-Invasive Biomarker for Chronic Periodontitis and Tooth Loss in Type 2 Diabetes - Sunila Bukanakere Sangappa; Harsha Mysore Babu; Ravindra C. Savadi; Praveen T. Krishnamurthy; Ammu V. V. V. Ravi Kiran (Wolters Kluwer Medknow Publications, 2024)
Background: Periodontitis and type 2 diabetes are chronic inflammatory diseases that increase inflammatory Interleukin-6 (IL-6) levels that induce the production of advanced glycation end products (AGEs) causing receptor activator of nuclear factor-kappa B ligand (RANKL) expression on osteoclasts, contributing to further alveolar bone destruction. Aim: To assess the role and diagnostic potential of salivary IL-6 (SIL-6) in the detection and evaluation of chronic periodontitis (CP) and tooth loss in type 2 diabetes mellitus (T2DM). Materials and Methods: This cross-sectional study comprised 240 subjects aged 30-69 years with minimum of 15 natural teeth. Fasting, unstimulated whole saliva was collected, full-mouth intra-oral examination and periodontal evaluation were performed using PCP-UNC 15 probe and glycaemic (HbA1c) levels were analysed by high-performance liquid chromatography (HPLC) method. Subjects were categorised into four groups of 60 participants each: Group 1 (controls); Group 2 (CP); Group 3 (T2DM with CP); Group 4 (T2DM with CP and tooth loss). Salivary IL-6 levels were quantitatively assessed by enzyme-linked immune sorbent assay method. Results: Average SIL-6 levels were significantly elevated in Group 4 (T2DM with CP and tooth loss) (P = 0.001) and in severe periodontitis (P = 0.001). Karl Pearson Correlation found a significant association between average SIL-6 and average periodontal pocket depth (APPD) (r = 0.180), average clinical attachment loss ≥3 mm (ACAL3) (r = 0.289) and severity of periodontitis (r = 0.3228). The receiver operating characteristic (ROC) curve depicted an overall sensitivity of 53.3%, specificity of 68.6% and accuracy of 60% in the detection and assessment of CP in T2DM with tooth loss. Conclusion: IL-6 in saliva is a valuable, non-invasive biomarker in the detection and evaluation of CP in T2DM with tooth loss.